Improving Students' Morals By Maximizing Inter-Personal Intelligence (Socializing) - Ratna Puspita; Agus Syukur (Universitas Muhammadiyah Tangerang, 2026)
This research is motivated by several factors, including the fact that many in our society still believe that a child's intelligence is limited to certain subjects. Furthermore, many parents and even teachers are unaware that a child's social skills are also considered intelligence, and if developed and maximized, they can become potential and professional skills. The purpose of this research is to stimulate a child's social intelligence in order to foster good morals among others. This is because moral activities are closely related to socializing.The method used in this research is qualitative with a descriptive approach. The results of this study indicate that a child's morals or ethics can be formed through interpersonal intelligence. From an Islamic perspective, a child's moral or ethical attitudes can be formed through their social interactions, their social environment, and their choice of friends. Someone with interpersonal intelligence can be directed to become a diplomat, legislator, motivator, community leader, and so on. In the school environment, this intelligence can be developed through various activities, such as discussions, comparative studies, group work, and so on.